Slow learners’ performance in solving mathematical problems in the inclusive classroom - Heni Yunilda Hasibuan; Cecep Anwar Hadi Firdos Santosa; Syamsuri Syamsuri (Jurnal Elemen, 2022)
Several studies have been carried out to uncover errors made by students in solving mathematical problems. However, there are few studies related to this kind of research specializing in students with special needs, in this case, slow learners, especially in Indonesia. In addition, the study did not classify the errors into the category of mathematical errors, so the location of the errors was not mapped. This study aimed to describe the performance of slow learners in solving mathematical problems, which are analyzed by the locations of errors based on the Newman procedure and categorized by Elbrink’s classification. This study also aimed to reveal the causes of errors made by slow learners in solving mathematical problems by confirming the characteristics of slow learners. The subject of this research was two eighth-graders who are considered slow learners in an inclusive junior high school. The data were collected through written tasks and semi-structured interviews. The results showed that both subjects could perform the reading and comprehension stages. However, they faced difficulties performing the transformation, process skills, and encoding that led to errors. The error categories were calculation, procedural, and symbolic errors. These errors were caused by the limited cognitive abilities of slow learners, their poor memory and concentration skills, and less variety of teaching methods by the teacher. The results of this study can become a reference for mathematics teachers to determine alternative strategies for overcoming errors made by slow learners in solving mathematical problems.